B.

From 1) (n-1)*n*(n+1) = 3*k

This is true for always for every value of n. Hence one cannot establish if n-1 is a multiple of 3. INSUFFICIENT

From 2) n (n+1) (n+1) = 3k.

Take some samples:

2*3*3 is a multiple of 3 but n-1 = 1 is not a multiple of 3.

3*4*4 is a multiple of 3 but n-1 = 2 is not a multiple of 3.

5*6*6 is a multiple of 3 but n-1 = 4 is not a multiple of 3.

6*7*7 is a multiple of 3 but n-1 = 5 is not a multiple of 3.

17*18*18 is a multiple of 3 but n-1 = 16 is not a multiple of 3.

Hence this eqn. is true for any n -1 where n-1 is not a multiple of 3. SUFFICIENT

P.S: It took me about 4 mins to get this one...

OA ?

_________________

Stay Hungry, Stay Foolish